Thioxopyrimidine in Heterocyclic Synthesis II: Novel Synthesis of Some Triazoles and Triazepine Derivatives with a Pyrimido[3,2:4,5]thieno[2,3-d]pyrimidine Skeleton - Yuh Wen Ho; Se Long Chou (Journal of Chemistry)
Condensation of ethoxymethyleneamino-thieno[2,3-d]pyrimidines 4 with appropriate amino compounds afforded the corresponding 7-substituted-8-imino-pyrimido[3,2:4,5]thieno[2,3-d]pyrimidines 6a, 6b, and 7 and 2-substituted-pyrimido[,:4,5]thieno[3,2-e][1,2,4]triazolo[1,5-c]pyrimidines 9a, 9b, respectively. Also, hydrazinolysis of compound 4 in ethanol which yielded the key intermediate 7-amino-8-imino-pyrimido[3,2:4,5]thieno[2,3-d]pyrimidine (10), which can be cyclized with appropriate isothiocyanates 14a–14g in refluxing pyridine, afforded the corresponding 2-(substituted-amino)-pyrimido[,:4,5]thieno[3,2-e][1,2,4]triazolo[1,5-c]pyramidines 15a–15g. Furthermore, intramolecular cyclization of compound (10) with appropriate 1,3-dibromopropane and Mannich bases 18a–18c under the basic condition afforded the corresponding (tri)dihydropyrimido[,:4,5]thieno[3,2:4,5]pyrimido[1,6-b][1,2,4]triazepines 16 and 18a–18c, respectively. On the other hand, the 11-substituted-pyrimido[,:4,5]thieno[3,2:4,5]pyrimido[1,6-b][1,2,4]triazepines 21a–21e were also obtained by the intramolecular cyclization of compound (10) with appropriate enaminone derivatives 19a–19e under the acidic condition.